2012
DOI: 10.1021/cn200083m
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Serotonin Modulate Human GABAρ1 Receptors Expressed in Xenopus laevis Oocytes

Abstract: GABAρ1 receptors are highly expressed in bipolar neurons of the retina and to a lesser extent in several areas of the central nervous system (CNS), and dopamine and serotonin are also involved in the modulation of retinal neural transmission. Whether these biogenic amines have a direct effect on ionotropic GABA receptors was not known. Here, we report that GABAρ1 receptors, expressed in X. laevis oocytes, were negatively modulated by dopamine and serotonin and less so by octopamine and tyramine. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
7
7
0
Order By: Relevance
“…As a consequence of this effect, dopamine relieved the GABAergic inhibition on the activity of third order retinal neurons. Consistent with these results is a recent finding that dopamine exerts a direct noncompetitive inhibition of human GABA ρ , but not GABA A receptors, expressed in Xenopus laevis oocytes [7]. The authors proposed that “the binding site for dopamine in GABAρ 1 receptor is different from the GABA binding site, and is probably not located inside the channel pore”.…”
Section: Introductionsupporting
confidence: 66%
“…As a consequence of this effect, dopamine relieved the GABAergic inhibition on the activity of third order retinal neurons. Consistent with these results is a recent finding that dopamine exerts a direct noncompetitive inhibition of human GABA ρ , but not GABA A receptors, expressed in Xenopus laevis oocytes [7]. The authors proposed that “the binding site for dopamine in GABAρ 1 receptor is different from the GABA binding site, and is probably not located inside the channel pore”.…”
Section: Introductionsupporting
confidence: 66%
“…We succeeded to prove the idea that serotonin could decrease the activity of GABA receptors, predominantly GABA C ones, which regulate the output of the main retinal neurons, the bipolar cells. In such a way, our results confirm the idea that serotonin can negatively modulate the GABA ρ receptors expression in Xenopus laevis oocytes [13]. Our results are in agreement with the data of some other authors who also showed reciprocal relations between the two systems in different brain regions [26,27].…”
Section: Resultssupporting
confidence: 93%
“…The aim of our study is to elucidate the putative interactions between these two retinal neurotransmitters systems. Based on the Ochoa-de la Paz et al's experiments, which showed that dopamine and serotonin may modulate negatively the GABA rho1 receptor expression in Xenopus laevis oocytes [13], we decided to study the interactions between serotonin -from one side, and the ionotropic GABA receptors -from other, in the retinas of the frog (Rana ridibunda) and the turtle (Pseudemys elegans). While the frog, a representative of class Amphybia, possesses mixed type of retina where both rod and cone photoreceptors are present, the turtle -belonging to class Reptilia, has predominantly cones in its retina.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the large number of serotonin receptors spread in the INL, it may be supposed that serotonin released by the retinopetal axons freely diffuses and binds to these receptors, exerting its effect as a neuromodulator. The negative neuromodulatory effect of serotonin on GABA ρ1 receptors has already been demonstrated on Xenopus laevis oocytes [61]. This is in conjunction with our understanding that serotonin serves not only as a neurotransmitter, but as a neuromodulator of the retinal function as well.…”
Section: Serotonin Receptorssupporting
confidence: 57%